Extracellular Matrix Orchestration of Tissue Remodeling in the Chronically Inflamed Mouse Colon - Moutin, Elisa B.; Bons, Joanna; Giavara, Giada; Lourenco, Filipe; Pan, Deng; Burton, Jordan B.; Shah, Samah; Colombé, Mathilde; Gascard, Philippe; Tlsty, Thea; Schilling, Birgit; Winton, Douglas J. (Cellular and molecular gastroenterology and hepatology, 2024)
Chronic inflammatory illnesses are debilitating and recurrent conditions associated with significant comorbidities, including an increased risk of developing cancer. Extensive tissue remodeling is a hallmark of such illnesses, and is both a consequence and a mediator of disease progression. Despite previous characterization of epithelial and stromal remodeling during inflammatory bowel disease, a complete understanding of its impact on disease progression is lacking. A comprehensive proteomic pipeline using data-independent acquisition was applied to decellularized colon samples from the Muc2 knockout (Muc2KO) mouse model of colitis for an in-depth characterization of extracellular matrix remodeling. Unique proteomic profiles of the matrisomal landscape were extracted from prepathologic and overt colitis. Integration of proteomics and transcriptomics data sets extracted from the same murine model produced network maps describing the orchestrating role of matrisomal proteins in tissue remodeling during the progression of colitis. The in-depth proteomic workflow used here allowed the addition of 34 proteins to the known colon matrisomal signature. Protein signatures of prepathologic and pathologic colitic states were extracted, differentiating the 2 states by expression of small leucine-rich proteoglycans. We outlined the role of this class and other matrisomal proteins in tissue remodeling during colitis, as well as the potential for coordinated regulation of cell types by matrisomal ligands. Our work highlights a central role for matrisomal proteins in tissue remodeling during colitis and defines orchestrating nodes that can be exploited in the selection of therapeutic targets. [Display omitted]